2018
DOI: 10.3390/geosciences9010008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Implicit and Explicit Vegetation Representations in SWAN Hindcasting Wave Dissipation by Coastal Wetlands in Chesapeake Bay

Abstract: Assessing the accuracy of nearshore numerical models—such as SWAN—is important to ensure their effectiveness in representing physical processes and predicting flood hazards. In particular, for application to coastal wetlands, it is important that the model accurately represents wave attenuation by vegetation. In SWAN, vegetation might be implemented either implicitly, using an enhanced bottom friction; or explicitly represented as drag on an immersed body. While previous studies suggest that the implicit repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…) into the wave action density spectrum balance equation. Recent studies (e.g., Baron-Hyppolite et al, 2018;Wu et al, 2016) have shown that this explicit vegetation representation in the SWAN model can produce reasonable simulation results that were in good agreement with field data and flume experiments.…”
Section: Coupling Seagrass Effects In Delft3dsupporting
confidence: 53%
See 1 more Smart Citation
“…) into the wave action density spectrum balance equation. Recent studies (e.g., Baron-Hyppolite et al, 2018;Wu et al, 2016) have shown that this explicit vegetation representation in the SWAN model can produce reasonable simulation results that were in good agreement with field data and flume experiments.…”
Section: Coupling Seagrass Effects In Delft3dsupporting
confidence: 53%
“…This approach adds a vegetation dissipation term which depends on vegetation height (hv), stem diameter (bv), shoot density ( N ), and vegetation wave drag coefficient (CDtrue∼) into the wave action density spectrum balance equation. Recent studies (e.g., Baron‐Hyppolite et al., 2018; Wu et al., 2016) have shown that this explicit vegetation representation in the SWAN model can produce reasonable simulation results that were in good agreement with field data and flume experiments.…”
Section: Methodsmentioning
confidence: 74%
“…Unfortunately, no more meteorological information is available. If we again compare the indices from Table 2 to those found in the literature such as Baron-Hyppolite et al (2019), we find comparable goodness of fit between modelled and measured waves.…”
Section: Wave Model Validationsupporting
confidence: 69%
“…The XBeach model can adequately predict wave attenuation after calibration of the bulk drag coefficient (van Rooijen et al 2016;Garzon et al 2019aGarzon et al , 2019b. The formulation by Mendez and Losada (2004) is also implemented in the SWAN model by Suzuki et al (2012) and several studies (e.g., Vuik et al 2016;Baron-Hyppolite et al 2019) have demonstrated that after calibration this extended SWAN model can adequately predict wave attenuation across a salt marsh.…”
Section: Appendix: Implementation Of Vegetation In the Xbeach Modelmentioning
confidence: 99%